ANALISIS ASPEK KESESUAIAN SYARIAH PADA INVESTASI SAHAM BERBASIS SECURITIES CROWDFUNDING - Utama, Sofyan Mei; Putra Ganda, Raka Angwas (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2022)
Securities crowdfunding is the activity of collecting funds from individuals or groups to fund an activity or business that uses information technology that will get reciprocity from the funds that have been given. One of the securities crowdfunding is that it can issue sharia securities and/or equity securities. This study aims to explain the mechanism and analysis of Islamic economic law regarding stock investment based on Securities Crowdfunding. The research method uses a normative juridical approach regarding norms or rules sourced from the DSN MUI Fatwa Number 140/DSN-MUI/VIII/2021 with the type of variant descriptive research method. The results of this study show that the stock investment mechanism brings organizers, issuers, and financiers in crowdfunding services to finance a project or an equity (share) business. In sharia economic law, stock investment based on securities crowdfunding is following all mechanisms, provisions, and implementation regarding stock investment in crowdfunding services or securities crowdfunding-based services in terms of the contracts used and prohibitions that should not be carried out in sharia principles and by the views of classical and contemporary jurisprudence scholars